Intensity of factor VIII treatment and the development of inhibitors in non‐severe hemophilia A patients: results of the INSIGHT case–control study. (2nd June 2017) - van Velzen, A. S.; Eckhardt, C. L.; Peters, M.; Leebeek, F. W. G.; Escuriola‐Ettingshausen, C.; Hermans, C.; Keenan, R.; Astermark, J.; Male, C.; Peerlinck, K.; le Cessie, S.; van der Bom, J. G.; et al.
Abstract : Essentials Research suggests that intensive treatment episodes may increase the risk to develop inhibitors. We performed an international nested case‐control study with 298 non‐severe hemophilia A patients. Surgery and a high dose of factor VIII concentrate were associated with increased inhibitor risk. Physicians need to review arguments for factor VIII dose and elective surgery extra critically. Summary: Background: Inhibitor development is a major complication of treatment with factor VIII concentrates in hemophilia. Findings from studies among severe hemophilia A patients suggest that intensive treatment episodes increase the risk of developing inhibitors. Objectives: We set out to assess whether intensive treatment is also associated with an increased risk of inhibitor development among non‐severe hemophilia A patients. Patients/Methods: We performed a nested case–control study. A total of 75 inhibitor patients (cases) and 223 control patients were selected from 2709 non‐severe hemophilia A patients (FVIII:C, 2–40%) of the INSIGHT cohort study. Cases and controls were matched for date of birth and cumulative number of exposure days (EDs) to FVIII concentrates. Conditional logistic regression was used to calculate both unadjusted and adjusted odds ratios (aOR); the latter were adjusted for a priori specified confounders. Results: Peak treatment of 5 or 10 consecutive EDs did not increase inhibitor risk (aOR, 1.0; 95% confidence interval (CI), 0.4–2.5; and aOR, 1.8; CI, 0.6–5.5, respectively). Both surgical intervention (aOR, 4.2; CI, 1.7–10.3) and a high mean dose (> 45 IU kg −1 /ED) of FVIII concentrate (aOR, 7.5; CI, 1.6–35.6) were associated with an increased inhibitor risk. Conclusions: Our findings suggest that high‐dose FVIII treatment and surgery increase the risk of inhibitor development in non‐severe hemophilia A. Together with the notion that non‐severe hemophilia A patients are at a lifelong risk of inhibitor development, we suggest that in the future physicians will review the arguments for the FVIII dose and elective surgery extra critically.